Agro-ecological approaches to pest management for sustainable agriculture - Parvatha Reddy, P. (Springer, 2017)
This book outlines a new paradigm, "Agro-ecological Intensification of Crop Protection", which reduces negative impacts on the environment and enhances the provision of ecosystem services. It discusses the use of ecologically based management strategies to increase the sustainability of agricultural production while reducing off-site consequences, highlighting the underlying principles and outlining some of the key management practices and technologies required to implement agro-ecological pest management. It also comprehensively explores important topics like stimulo-deterrent diversion strategy, precision agriculture, plant breeding, nutrient management, habitat management, cultural approaches, cultivar mixtures/multiline cultivars, crop rotation, crop residue management, crop diversity, cover crops, conservation tillage, biofumigation, agro-forestry, and addition of organic matter. This timely book promotes the rapid implementation of this technology in farming community around the globe. It is a valuable resource for the scientific community involved in teaching, research and extension activities related to agro-ecological pest management as well as policymakers and practicing farmers. It can also be used for teaching post-graduate courses.
Keywords: Agricultural pests -- Control.; Sustainable agriculture.; elektronické knihy; electronic books